(untitled) - Yvonne Lefèber (Groningen, The Netherlands, 1994)
The book compares the role, practices and beliefs of TBAs in different countries of Africa, Asia and Latin America; broads the insights into traditional midwifery in these countries by classifying the practices and beliefs of TBAs according to the common obstetrical classifications; and gives suggestions for health policy with reference to the training of TBAs
Keywords: midwifery,midwives - africa,midwives - asia,midwives - latin america,obstetrics